1991
DOI: 10.1111/j.1365-2796.1991.tb00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis in adults: analysis of 777 patients

Abstract: A total of 777 patients with thrombocytosis, defined as a platelet count of greater than 500 x 10(9)l-1, seen in a University hospital over a 1-year period, were studied prospectively for aetiology. The most frequent causes of thrombocytosis were infection (21.9%), rebound thrombocytosis (19.4%), tissue damage (17.9%), chronic inflammatory disorders (13.1%) and malignancy (5.9%). Thrombocytosis associated with multiple causative factors, occurring simultaneously, was seen in 6.1% of cases. Thrombocytosis of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 10 publications
7
38
0
3
Order By: Relevance
“…Inflammatory reactions involving cytokines take place in patients with active IBD [8], and it has been demonstrated that interleukin-6 (IL-6), which is a mediator of inflammation, is associated with activation of the coagulation pathway [7]. IL-6 stimulates the release of thrombopoietin and induces thrombocytosis in patients with inflammatory disease [8], and reactive thrombocytosis is a typical feature in IBD [14]. Infusion of recombinant IL-6 stimulates coagulation activation [7] and is associated with a decreased capacity of the anticoagulant system in patients who suffered an acute stroke [15].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory reactions involving cytokines take place in patients with active IBD [8], and it has been demonstrated that interleukin-6 (IL-6), which is a mediator of inflammation, is associated with activation of the coagulation pathway [7]. IL-6 stimulates the release of thrombopoietin and induces thrombocytosis in patients with inflammatory disease [8], and reactive thrombocytosis is a typical feature in IBD [14]. Infusion of recombinant IL-6 stimulates coagulation activation [7] and is associated with a decreased capacity of the anticoagulant system in patients who suffered an acute stroke [15].…”
Section: Introductionmentioning
confidence: 99%
“…Thrombocytosis has been shown to be associated with infectious disease, tissue damage, and chronic inflammatory disorders [5]. In malignant disease, thrombocytosis is thought to be secondary to an increased rate of platelet production with no alteration in platelet survival [6].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas primary thrombocytosis is observed in myeloproliferative syndromes, secondary or reactive thrombocytosis is noted in numerous clinical situations, 1 especially in association with inflammatory states of either infectious or noninfectious origin such as trauma and malignancy. 2,3 The extent to which mediators of the immune or hematopoietic system are involved in the regulation of the circulating platelet count in these conditions is insufficiently understood.Interleukin-6 (IL-6) plays a prominent role in inflammatory and neoplastic diseases. 4-6 Accordingly, mice deficient in IL-6 show a severely impaired acute-phase response.…”
mentioning
confidence: 99%